Pengembangan Ekonomi Kreatif Dari Bahan Limbah (Kain Perca) Melalui Platform Digital - Andani Asmara; Rudi Rinaldo; Muhammad Afriusnaldi; Ananda Enda Nadicca; Iko Marsela (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to analyze the development of the creative economy through the utilization of textile waste, particularly patchwork fabric, by leveraging digital platforms. Employing a qualitative approach with a case study method, the research involved creative entrepreneurs who transform patchwork waste into economically valuable products, such as bags, wallets, accessories, and home decorations. Data were collected using in-depth interviews, participatory observation, and document studies, and then analyzed thematically. The findings reveal that patchwork fabric waste can be successfully converted into high-value creative products through innovative designs and diversification strategies. Furthermore, the adoption of digital platforms, including social media and online marketplaces, plays a pivotal role in product promotion, enhancing brand awareness, and expanding market reach beyond local boundaries. This integration not only provides economic benefits, such as increased income for entrepreneurs and the creation of new job opportunities, but also fosters social and environmental impacts, including raising community awareness of sustainable waste management practices. The study emphasizes that the creative transformation of textile waste contributes to circular economy principles, supporting resource efficiency and reducing environmental burden. In conclusion, the integration of creativity, innovation, and digital technology utilization emerges as a sustainable strategy for developing a creative economy based on waste materials. These findings provide insights for entrepreneurs, policymakers, and communities in promoting environmentally friendly business models while simultaneously driving inclusive economic growth.